Study on Mix Ratio of Lightweight Aggregate Concrete for BRB Application - Chen, Yongxu; Song, Xiaosheng (International Journal of Materials Science and Technology Studies, 2024)
As a new type of energy dissipation damping mechanism widely used in recent years, anti-buckling bracing still has some shortcomings such as self-importance. In this paper, the composition of anti-buckling support, its working principle and weight reduction ideas and methods are explained first, and then the test process and methods of light aggregate are described, and then the possible problems of light anti-buckling support are explained, and finally the possible problems are put forward for practical application.